Identification of Compounds That Inhibit IGF-I Signaling in Hyperglycemia. (7th December 2009) - Maile, Laura A.; Allen, Lee B.; Veluvolu, Umadevi; Capps, Byron E.; Busby, Walker H.; Rowland, Michael; Clemmons, David R.
Abstract : Increased responsiveness of vascular cells to the growth factor IGF-I has been implicated in complications associated with diabetes. Here we describe the development of an assay and screening of a library of compounds for their ability to accelerate cleavage of the transmembrane protein integrin-associated protein (IAP) thereby disrupting the association between IAP and SHPS-1 which we have shown as critical for the enhanced response of vascular cells to IGF-I. The cell-based ELISA utilizes an antibody that specifically detects cleaved, but not intact, IAP. Of the 1040 compounds tested, 14 were considered active by virtue of their ability to stimulate an increase in antibody-binding indicative of IAP cleavage. In experiments with smooth muscle and retinal endothelial cell cultures in hyperglycemic conditions, each active compound was shown to accelerate the cleavage of IAP, and this was associated with a decrease in IAP association with SHPS-1 as determined by coimmunoprecipitation of the proteins from cell lysates. As a consequence of the acceleration in IAP cleavage, the compounds were shown to inhibit IGF-I-stimulated phosphorylation of key signaling molecules including Shc and ERK1/2, and this in turn was associated with a decrease in IGF-I-stimulated cell proliferation. Identification of these compounds that utilize this mechanism has the potential to yield novel therapeutic approaches for the prevention and treatment of vascular complications associated with diabetes.